Hydrocephaly and secondary intracranial hypertension to racemosa neurocysticercosis - Sampaio, Patrick Giordanni Gomes; Maracajá, Hiago Diniz; Temoteo, Túlio Carneiro Monteiro; Figueiredo, Sara Raquel Nóbrega; Batista, Francielle Lopes de Araújo (Headache Medicine, 2021)
Case report G.F.M, 71 years old, male, farmer, presented a history of holocranial headache of a pulsatile type, more intense on waking, and associated with photophobia. The complaint lasted six months. He also reported episodes of tinnitus and unilateral hearing loss on the left. After conducting screening tests in the emergency department, communicating hydrocephalus and cystic lesions were found in the subarachnoid and intraparenchymal space. In the neurological examination, the positive data were bilateral papilledema and hearing loss in the left boné conduction. Given these findings, the racemous variant of neurocysticercosis and secondary hydrocephalus was suspected, causing intracranial hypertension. Thus, it was decided to start specific treatment with albendazole 15 mg/kg/day (two daily doses), associated with praziquantel 50 mg/kg/day (three daily doses), for 14 days. To reduce the inflammatory process of the lesions, it was proposed to keep the patient on dexamethasone 8 mg/day for 90 days. In addition to this scheme, topiramate 100 mg/day associated with acetazolamide 1 g/day was started, along with serial lumbar puncture to relieve intracranial pressure. Conclusion The combination of modern diagnostic tests, use of antiparasitic drugs, optimization of anti-inflammatory treatments and minimally invasive neurosurgical procedures have improved results in patients with NCC. Even so, this is the helminth infection that most affects the CNS and represents a major public health problem in most parts of the world, since it remains a neglected pathology, like so many other parasites, given that it is susceptible to containment through simple preventive actions as well as eradication.